A novel index retrieval and query optimisation method for private information retrieval in location-based service application. (8th September 2021) - Kumar, K.M. Mahesh; Bhat, Radhakrishna; Sunitha, N.R.
Location-based service is a popular information and communications technology. Security, trust and privacy are the major concerns preventing the wide deployment of LBS. In this paper, we address privacy issues by employing computational private information retrieval schemes and highlight a few optimisation methods. We propose a novel index retrieval technique which helps the user to identify his grid ID and know the index value for the point-of-interest (POI) type of his interest, and an adaptive computation method (flip-optimisation) to reduce multiplication cost for PIR query used to retrieve the POI item at the specified index. The adaptive computation method proposed in this paper is generic and can be applied to any application which uses PIR protocol to access data privately. Our work empirically evaluated the proposed method by implementing the PIR prototype and found it suitable for a practical purpose.